Operationalizing Maqāṣid al-Sharīʿah in Islamic Finance: Pathways to Poverty Alleviation and Sustainable Development - Muhammad Jibril, Abubakar (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2025)
This article examines how maqāṣid al-sharīʿah (the higher objectives of Islamic law) can be operationalized within Islamic finance to advance poverty alleviation and sustainable development. While existing s cholarship extensively theorizes maqāṣid compliance, it remains largely normative and offers limited empirical guidance on how Islamic financial instruments translate maqāṣid principles into measurable socio-economic outcomes. Drawing on the classical frameworks of al-Ghazālī and al-Shāṭibī and engaging contemporary development policy discourse, the study analyzes how the five maqāṣid protection of religion, life, intellect, lineage, and property can inform ethical and impact-oriented financial reform. Methodologically, the study adopts a qualitative integrative approach combining doctrinal legal analysis, policy review, and comparative case studies of Islamic finance practices in Malaysia, Ethiopia, and Indonesia, with data drawn from statutes, regulatory frameworks, institutional reports, and scholarly literature, analyzed through thematic and comparative techniques. The findings indicate that (i) zakāt and waqf schemes contribute to the protection of life and intellect through access to health care and education, (ii) takaful mechanisms strengthen lineage and social security by mitigating household vulnerability, and (iii) maqāṣid-oriented microfinance enhances protection of property by promoting equitable wealth circulation. The article contributes original value by moving beyond formal Sharīʿah compliance to propose a maqāṣid-based evaluative lens that links Islamic financial governance to concrete development outcomes, positioning Islamic finance as a viable framework for justice-centered and sustainable economic transformation. maqāṣid-oriented microfinance enhances protection of property by promoting equitable wealth circulation. The article contributes original value by moving beyond formal Sharīʿah compliance to propose a maqāṣid-based evaluative lens that links Islamic financial governance to concrete development outcomes, positioning Islamic finance as a viable framework for justice-centered and sustainable economic transformation.